Association of Pretransplant Renal Function With Liver Graft and Patient Survival After Liver Transplantation in Patients With Nonalcoholic Steatohepatitis. Issue 3 (28th February 2019) - Molnar, Miklos Z.; Joglekar, Kiran; Jiang, Yu; Cholankeril, George; Abdul, Mubeen Khan Mohammed; Kedia, Satish; Gonzalez, Humberto C.; Ahmed, Aijaz; Singal, Ashwani; Bhamidimarri, Kalyan Ram; Aithal, Guruprasad Padur; Duseja, Ajay; et al.
Abstract : Nonalcoholic steatohepatitis (NASH) is one of the top 3 indications for liver transplantation (LT) in Western countries. It is unknown whether renal dysfunction at the time of LT has any effect on post‐LT outcomes in recipients with NASH. From the United Network for Organ Sharing–Standard Transplant Analysis and Research data set, we identified 4088 NASH recipients who received deceased donor LT. We divided our recipients a priori into 3 categories: group 1 with estimated glomerular filtration rate (eGFR) <30 mL/minute/1.73 m 2 at the time of LT and/or received dialysis within 2 weeks preceding LT (n = 937); group 2 with recipients who had eGFR ≥30 mL/minute/1.73 m 2 and who did not receive renal replacement therapy prior to LT (n = 2812); and group 3 with recipients who underwent simultaneous liver‐kidney transplantation (n = 339). We examined the association of pretransplant renal dysfunction with death with a functioning graft, all‐cause mortality, and graft loss using competing risk regression and Cox proportional hazards models. The mean ± standard deviation age of the cohort at baseline was 58 ± 8 years, 55% were male, 80% were Caucasian, and average exception Model for End‐Stage Liver Disease score was 24 ± 9. The median follow‐up period was 5 years (median, 1816 days; interquartile range, 1090‐2723 days). Compared with group 1 recipients, group 2 recipients had 19% reduced trend for risk for death with a functioning graft (subhazard ratio [SHR], 0.81; 95% confidence interval [CI], 0.64‐1.02) and similar risk for graft loss (SHR, 1.25; 95% CI, 0.59‐2.62), whereas group 3 recipients had similar risk for death with a functioning graft (SHR, 1.23; 95% CI, 0.96‐1.57) and graft loss (SHR, 0.18; 95% CI, 0.02‐1.37) using an adjusted competing risk regression model. In conclusion, recipients with preserved renal function before LT showed a trend toward lower risk of death with a functioning graft compared with SLKT recipients and those with pretransplant severe renal dysfunction in patients with NASH.